The influence of health-improving fitness classes on the degree of fat deposition in women of the second mature age - Olha Podrihalo; Władysław Jagiełło; Leonid Podrigalo; Sergii Iermakov; Tetiana Yermakova (IP Iermakov S.S., 2022)
Background and Study Aim. Purpose of the research: analysis of the influence of health-improving fitness classes of various orientations on the degree of fat deposition in women of the second mature age. Material and Methods. Participants: group 1 - 40 women, (43.33 ± 0.93) years, group 2 - 25 women, (44.40 ± 0.93) years. The participants trained for 8 months, three times a week for 1 hour. Group 1 - classes in dance aerobics (Monday), strength fitness (Wednesday) and stretching (Friday). Group 2 - stretching only. Before the start and after the end of the program, the body weight and length were determined, the degree of fat deposition using a calipermeter at 17 points, the body mass index was calculated. Results. In group 1, there was a significant decrease in body weight, BMI, a decrease in the thickness of skin and fat folds at all points. In group 2, a significant decrease in body weight, BMI, a decrease in the thickness of folds at 13 points in 60-96% of participants was established. At the end of the study, group 1 had a smaller size of the folds of the thighs and left forearm compared to group 2. Regular exercise leads to a decrease in body weight BMI, a decrease in body fat. Complex classes have a more pronounced effect compared to stretching. This type of training is more effective in terms of the dynamics of the criteria used and the number of participants with the established changes. The sessions provided an increase in the number of persons with a normal BMI and a decrease in the number of obese participants. Conclusions. The applied indicators and methods can be recommended for use in health monitoring in health fitness.